Assessment of Soil Organic Carbon in Tropical Agroforests in the Churiya Range of Makawanpur, Nepal - Lilu Kumari Magar; Gandhiv Kafle; Pradeep Aryal (International Journal of Forestry Research)
This paper reports the findings of a research study conducted in three tropical agroforestry systems in the Makawanpur district of Nepal, to quantify the spatial and vertical distribution of soil organic carbon in 30 cm soil profile depth in agrisilviculture, home garden, and silvopasture. The three agroforestry systems represent tropical agroforests of Nepal. It was found that the soil had 24.91 t/ha soil organic carbon in 30 cm soil profile in 2018, with 2.1% soil organic matter concentration in average. Bulk density was found increasing with an increase in soil depth. The soil organic carbon was not found significantly different across different agroforestry systems. Looking into the values of stocks of soil organic carbon, it is concluded that the tropical agroforests have played a role in global climate change mitigation by storing considerable amounts of soil organic carbon and the storage capacity can further be increased. Involvement of farmers in the management of tropical agroforests cannot be ignored in the process of climate change mitigation.